MALDI-TOF mass spectrometry of saliva samples as a prognostic tool for COVID-19 - Lazari, Lucas C.; Zerbinati, Rodrigo M.; Rosa-Fernandes, Livia; Santiago, Veronica Feijoli; Rosa, Klaise F.; Angeli, Claudia B.; Schwab, Gabriela; Palmieri, Michelle; Sarmento, Dmitry J. S.; Marinho, Claudio R. F.; Almeida, Janete Dias [UNESP]; To, Kelvin; et al. (Taylor & Francis, 2022)
Background: The SARS-CoV-2 infections are still imposing a great public health challenge despite the recent developments in vaccines and therapy. Searching for diagnostic and prognostic methods that are fast, low-cost and accurate are essential for disease control and patient recovery. The MALDI-TOF mass spectrometry technique is rapid, low cost and accurate when compared to other MS methods, thus its use is already reported in the literature for various applications, including microorganism identification, diagnosis and prognosis of diseases. Methods: Here we developed a prognostic method for COVID-19 using the proteomic profile of saliva samples submitted to MALDI-TOF and machine learning algorithms to train models for COVID-19 severity assessment. Results: We achieved an accuracy of 88.5%, specificity of 85% and sensitivity of 91.5% for classification between mild/moderate and severe conditions. When we tested the model performance in an independent dataset, we achieved an accuracy, sensitivity and specificity of 67.18, 52.17 and 75.60% respectively. Conclusion: Saliva is already reported to have high inter-sample variation; however, our results demonstrates that this approach has the potential to be a prognostic method for COVID-19. Additionally, the technology used is already available in several clinics, facilitating the implementation of the method. Further investigation using a larger dataset is necessary to consolidate the technique.
Keywords: biomarkers; prognosis; proteomics; Saliva; SARS-CoV-2